Greener pastures of home: an ethnographic study on everyday sustainable practices in Nyanga, Cape Town - Lukas, Megan (Department of Environmental and Geographical Science, 2021)
Most contemporary urban development in cities of the global South is responding to rapid urbanisation caused by prospects of employment opportunities and improved quality of life. Research in the field of sustainability in cities of the global South mainly focuses on economic and social development goals. However, there is an emerging sense that an appreciation of ordinary, everyday practices at the level of the community is important for developing a nuanced understanding of what sustainability might be in Southern cities. There is agreement on the need to pay attention to social and cultural practices in urban sustainability literature; yet relatively little research in the field engages closely with everyday practices at the level of neighbourhoods or communities. This is particularly true in the global South, and especially in low-income urban neighbourhoods, where developmentalist agendas dominate both academic and policy-related research. My thesis addresses this gap through an exploration of a wide range of everyday practices in a lowincome, peri-urban area, which happen to have sustainable effects. Analysing ethnographic data collected over nine months in the Cape Town township of Nyanga, I find that the desire of urban residents to create spaces of home and belonging drives behaviour that in fact has positive sustainable outcomes, yet is seldom considered in literature on sustainable cities. I argue that paying attention to how ordinary citizens ‘make home', specifically by (i) drawing on memories, (ii) developing livelihoods, and (iii) building social relations can enrich understanding not only of economic and social development but also of the complex ways in which social and environmental sustainability are already intertwined in everyday practice. Facilitating sustainable spaces in cities of the global South, therefore, requires critical engagement with the practices that are already taking place in urban residents' everyday lives.